Patient and public involvement in the co-design and assessment of unobtrusive sensing technologies for care at home: a user-centric design approach - Jenny Sharma; Nazia Gillani; Imran Saied; Aaesha Alzaabi; Tughrul Arslan (BMC Geriatrics)
Abstract Background There is growing interest in developing sensing solutions for remote health monitoring to support the safety and independence of older adults. To ensure these technologies are practical and relevant, people-centred design is essential. This study aims to explore the involvement of various stakeholders across different developmental stages to inform the design and assess the capabilities of unobtrusive sensing solutions being developed as part of the Advanced Care Research Centre (ACRC), Edinburgh, UK. Methods This study was conducted in two phases. In Phase I (Ideation), discussions were held with stakeholders (n = 19), including senior geriatricians (n = 2), healthcare and care home professionals (n = 4), PPI experts (n = 2), researchers (n = 4) and public members aged 65 and above from the ACRC Patient and Public Involvement (PPI) Network (n = 7). The goal was to identify clinically significant health parameters and design preferences. Based on this, prototypes of unobtrusive sensors for monitoring movement, hydration, and respiration were developed. In Phase II (Development and Co-Design), an in-person PPI workshop was conducted with PPI experts (n = 2), researchers (n = 4) and PPI members (n = 8). The developed prototypes were demonstrated, and qualitative feedback was collected through focus group discussions on themes such as acceptability, usability, privacy, data sharing, and functionality enhancement. Results Stakeholder input from Phase I emphasized the importance of non-contact sensing technologies that maintain privacy. Movement, hydration, and respiration were identified as critical health parameters. In Phase II, PPI members were optimistic about the prototypes, valuing their unobtrusive design and privacy-preserving features. Key themes identified included (1) the need for user-customized alarms, (2) clear data-sharing protocols, and (3) the importance of embedding sensors into familiar household objects. Suggestions for refining the prototypes included adding functionality for detecting deviations in daily routines and integrating feedback mechanisms for caregivers. Conclusions Involving diverse stakeholders from the early stages of technology development enhanced the relevance and acceptability of unobtrusive sensing solutions. This study highlights the importance of integrating public perspectives into the design process. For successful implementation, developers of healthcare technologies should prioritize privacy, usability, and clear communication with end-users and caregivers.